High light intensity enhances cannabinoid biosynthesis through concerted gene expression in hemp (Cannabis sativa) flowers - Hahm, Seungyong; Bok, Gwonjeong; Kim, Sungjin; Kim, Byungjun; Lee, Yongjae; Kim, Sunwoo; Park, Jongseok (Frontiers in Plant Science, 2025)
IntroductionResearch on optimizing light intensity to maximize phytochemical production during hemp flowering is limited, despite growing global demand. We investigated the effects of light-emitting diode (LED) intensity on hemp growth, cannabinoid content, and gene expression.MethodsHemp plants (Cannabis sativa 'Queen Dream') were grown under white LEDs at light intensities of 200, 400, and 600 μmol·m−2·s−1 with a 12/12 h photoperiod for 35 days during the flowering stage.ResultsThe dry mass of stems, leaves, and flowers increased linearly with increasing light intensity. Cannabinoid analysis revealed that levels of cannabidiol (CBD), cannabidiolic acid, and tetrahydrocannabinolic acid increased linearly with light intensity, reaching the highest levels at 600 μmol·m−2·s−1. Total CBD increased by 36.88% at 600 μmol·m−2·s−1 compared to 200 μmol·m−2·s−1. CBD yield per plant also increased linearly across the entire light intensity range. Gene expression analysis revealed a coordinated upregulation of genes involved in the hexanoate–olivetolic acid–cannabigerolic acid–cannabinoid biosynthesis pathway under high light intensity, with a notable increase in cannabidiolic acid synthase (CBDAS) expression.ConclusionThese findings demonstrate that a light intensity of 600 μmol·m−2·s−1 effectively enhances both biomass and cannabinoid accumulation at the flowering stage, providing valuable insights for controlled-environment hemp cultivation aimed at maximizing CBD yield.